Comic books and graphic novels for young adults in selected secondary private school libraries in Malabon City with implications towards an encompassing collection development policy - De Castro, A.B. Gideon N. (2015)
People nowadays can choose assorted types of entertainment through different forms of media. Comic books and graphic novels fall short in terms of educational value compared to reference materials, especially in school libraries. This study therefore seeks to develop an encompassing collection development policy which aims to include comic books and graphic novels in the library collection in consonance to the preference of young adults in Malabon City which are St. Therese of the Child Jesus Academy, Philippine Malabon Cultural Institute, and St. James Academy.